A review on potentials and challenges of nanolubricants as promising lubricants for electric vehicles. (16th September 2021) - Ahmed Abdalglil Mustafa, Waleed; Dassenoy, Fabrice; Sarno, Maria; Senatore, Adolfo
Abstract: The most remarkable difference between electric vehicles (EVs) and conventional ones is the fuel burning dependency of the internal combustion engine, while the emerging EVs operate on electric motors. These alternations create staggering shifts in both lubricants' market demand and performance specifications. Lubricants for electrical powertrain constitutes greases, transmission oils, and lubricants for auxiliary systems and do not rely on engine oils as internal combustion vehicles. The new standards will be more focused on lubricants' electrical properties such as breakage voltage and conductivity, coupled with tribological performance under high rpm, corrosion resistance and thermal management benchmarks. This paper thematically reviews the different studies performed with nanolubricants, and how they match EVs' operational requirements. Conclusions from this study can be considered as guidelines for the potential application of nanolubricants in EVs and possible future research that can be accomplished on the topic.